Regularized Adversarial Training for Robust CNN Image Classification: Evaluation of ATWR, ATGR, and EATR Under White-Box Attacks - Pham, Thi Thanh Thuy; Ho, Bao-Chau; Doan, Huong-Giang (Informatica, 2025)
Adversarial attacks pose serious challenges to the robustness of deep Convolutional Neural Networks (CNNs) in image classification. In this study, we evaluated the vulnerability of popular CNN modelsResNet50, ResNet101, AlexNet, MobileNetV2, DenseNet121, and InceptionNetV3-under white-box attacks, including FGSM, PGD, BIM, and C&W. Experiments are conducted on standard datasets such as MNIST, CIFAR-10, CIFAR-100, and ImageNet. To enhance model robustness, we propose three regularized adversarial training methods: ATWR (Adversarial Training with Weight Regularization), ATGR (Adversarial Training with Gradient Regularization), and EATR (Ensemble Adversarial Training with Regularization). Our results show that ATWR reduces the accuracy drop under the PGD attack on CIFAR-10 from 65.93% to 0.00%, and under C&W attack on MNIST from 100% to 0.31%. EATR achieves consistent robustness across all attacks and models, reducing the accuracy drop in CIFAR-10 (PGD) from 65.93% to 0%, while maintaining the classification accuracy within 10% of the original. ATGR, while reducing classification accuracy, enhances adversarial detection by amplifying the difference in output behavior under attack. The proposed methods strike varying trade-offs between robustness, generalization, and detectability. These findings offer practical guidance for securing deep CNNs against strong white-box adversarial threats. The source codes are available at: https://github.com/AdversarialAttack/DefenseAndAttack.